A Meta-analysis of Bentonite Efficacy on Performance, Carcass Yield, Giblet, and Blood Constituents of Broiler Fed Contaminated Aflatoxin - Ergin Öztürk; Anuraga Jayanegara; Arif Darmawan (Journal of Agricultural Sciences)
Aflatoxins can easily grow and develop in many feed ingredients and influence the risk of several animal chronic diseases. The present study aimed to evaluate the effect of bentonite inclusion on performances, carcass yield, giblet, and blood constituents of broiler-fed contaminated aflatoxin through a meta-analytical approach. A database was developed based on scientific publications that were searched using several search tools such as Science Direct, PubMed, Scopus, and Google Scholar with “bentonite”, “clay”, “montmorillonite”, “aflatoxin” and “broiler” as keywords. A total of 31 studies were retrieved and included in the analysis. Data analysis was based on the mixed model in which dietary bentonite inclusion was treated as the fixed effect and different studies were considered as random effects. Bentonite used were sodium bentonite, calcium bentonite, and montmorillonite form with levels ranging from 0 to 5%. Meanwhile, aflatoxin B1 levels in the diet ranged from 0 to 5 mg/kg. In this study, body weight gain, feed intake, and feed efficiency showed a linear increase (p<0.001) in all phases. The mortality rate linearly decreased (p<0.05) in the cumulative. Bentonite inclusion linearly increased (p<0.001) the carcass, breast, leg, bursa of Fabricius, and gizzard weight proportion. The percentage of kidney, liver, heart, pancreas, uric acid, and gamma-glutamyltransferase linearly decreased (p<0.001) by increasing bentonite levels. Dietary bentonite linearly increased (p<0.001) total protein, albumin, aspartate aminotransferase, calcium, glycogen, globulin, and hemoglobin (p<0.05). It was concluded that bentonites have the ability to eliminate the detrimental effects of aflatoxin, which may increase the broiler performance, carcass yield and prevent the change in abnormal giblet weight. For effectiveness and animal safety, the EFSA recommends using a maximum of 2% bentonite in the feed.